PERAN ORANGTUA TERHADAP PENDIDIKAN AGAMA ANAK DI DESA SAWAH KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Rahmah "; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The research purpose to determine the role of parents and religious behavior of children with analyze correlation between the role of parents and religious behavior of children. Role is pattern of behavior or action should be taken by parents in educating children religion. This research conducted at the northern Kampar district Sawah subdistrict Kampar. Population of this research is all heads of families residing in the village Sawah field north of Kampar districts and have children aged adolescent age range 13-15 years who attend school or junior high school equivalent listed in the records of population. There are some elements in this research, the first provides religious education which includes about doing prayers, fasting in Ramadan, reciting Al-Quran, gave infak and respect for older people. The second control the implementation of the child worship, control activities carried out by taking action if children do not practice their religion. Third, encourage children to worship that parents set an example and encourage children worship together. Fourth, be patient that parents are expected to be patient in educating religious behavior of children. This research technique is descriptive quantitative, to describe the results of research in the field with numbers, then described by words or narration. Based on the research in the field found that role of parents in Sawah village is considered to be good for 91,48%, the education of children in the Sawah village also rated as good by 95%, there is a strong correlation between the role of parents to religious education of children with result is 0,9 and a significant correlation of 0,01, means there is significant correlation between the role of parents to religious education of children.Key words: Role, Parents, Religious Education, Children